HSP70-Mediated Autophagy-Apoptosis-Inflammation Network and Neuroprotection Induced by Heat Acclimatization - Yuchen Su; Xinyan Zheng (Biology, 2025)
Global warming has intensified the health risks associated with heat stress, such as heatstroke and dehydration, underscoring the importance of understanding heat acclimatization (HA). HA involves physiological, psychological, and structural adaptations to prolonged high temperatures, improving heat tolerance and reducing heat-related harm. A key player in this process is HSP70, a conserved protein essential for maintaining cellular balance, regulating cell death, and controlling waste removal. While HA mechanisms like temperature regulation and metabolic changes are well studied, the relationship between HSP70 and brain self-repair processes remains unclear. This study uncovers how HSP70, and these processes work together to aid heat adaptation, reveals how environmental stress drives inherited resilience through genetic adjustments, and offers insights for designing targeted health strategies to protect vulnerable populations, connecting lab discoveries to global health needs.